Seasonal Immune Rhythms of head kidney and spleen cells in the freshwater Teleost, Channa punctatus - Rakesh Kumar Chandra; Ajay Kumar Bhardwaj; Atanu Kumar Pati; Manish Kumar Tripathi (Fish and Shellfish Immunology Reports, 2023)
Annual rhythms in immune function are the reflection of a crucial physiological strategy to deal with environmental stressors. The fish are pivotal animal models to study the annual rhythm and to understand the evolution of the vertebrate biological system. The current research was planned to assess the annual changes in the innate immune functions of immune cells in a teleost, Channa punctatus. Head kidney and splenic macrophage phagocytosis, superoxide generation, and nitrite release were evaluated to assess innate immunity. Cell-mediated immunity was measured through head kidney and splenic lymphocyte proliferation in presence of mitogens. The superoxide anion generation by the cells of head kidney and spleen was maximum in October. A bimodal pattern in nitrite production was observed with the first peak in November and the second in March. Cosinor analysis revealed a statistically significant annual rhythm in nitrite production. Similarly, phagocytosis and lymphocyte proliferation also showed statistically significant annual rhythms. It was concluded that animals maintain an optimum immune response in seasonally changing environments. Elevated immunity during certain times of the year might assist animals deal with seasonal environmental stressors. Further research may be focused upon measuring survival rate and reproductive success after season induced elevated immunity.